Effectiveness of Land Mafia Task Force in Prevention and Eradication of Land Mafia in Indonesia - Sulastri, Lusia (KRTHA BHAYANGKARA, 2025)
Various problems and issues of land conflict in Indonesia are caused by many parties who often commit land misappropriation or the popular term land mafia. To answer this problem, the S task force Mafia​ Land, but in reality land conflicts due to land mafia continue to occur. Therefore, this study examines the effectiveness of the Land Mafia Task Force in preventing and eradicating land mafia in Indonesia and the factors that hinder the performance of the Land Mafia Task Force in preventing and eradicating land mafia in Indonesia. The results of the study indicate that the Land Mafia Task Force in preventing and eradicating land mafia in Indonesia has not been fully effective. Factors that hinder the performance of the land mafia task force in preventing and eradicating land mafia in Indonesia include the absence of legal regulations that cover the eradication of land mafia perpetrators, the unsynchronized task force established in each institution, the absence of a special budget provided for eradicating land mafia, the community is still unfamiliar with agrarian law and a culture of legal awareness regarding land that has not been built.